The Gains from Limited Trade - Child, F. C. (Review of Economic Studies, 1950)
Journal Article The Gains from Limited Trade Get access F. C. Child F. C. Child Williamstown, Mass., U.S.A. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 18, Issue 2, 1950, Pages 87–98, https://doi.org/10.2307/2295796 Published: 01 April 1950